Bone recurrence rarely seen in endometrial cancer and review of the literature. Issue 6 (13th April 2016) - Kimyon, Gunsu; Karalok, Alper; Basaran, Derman; Ureyen, Isin; Celik, Mehmet; Tasci, Tolga; Tulunay, Gokhan; Turan, Taner
Abstract: Aim: To evaluate the clinical findings and treatment results of patients with endometrial cancer (EC) who experienced initial recurrence or progression in bones. Methods: Ten EC patients experiencing initial recurrence or disease progression in bones were included in the study. Disease recurrences located in a single bone and in more than one bone were defined as single localization bone recurrence (BR) and multiple localization BR, respectively. Time from initial surgery to BR was determined as disease‐free interval (DFI) and time from BR to death or last contact with a patient was described as post‐recurrence survival (PRS). Results: Seven of 10 patients were asymptomatic. The median DFI was 13 months (range: 2–68). While eight patients had isolated BR, two patients also had concurrent extraosseous recurrences. Five patients had single and four patients had multiple localization BR. The most common sites for BR were the femur (55.5%) and vertebra (44.4%). Two‐year PRS was 37.5% in all patients and 50% in patients with endometrioid EC. None of the patients with non‐endometrioid type EC survived. In patients with multiple localization BR and with recurrence only occurred in the bones, two‐year PRS was 75% and 50%, respectively. None of the patients with BR with extraosseous involvement survived beyond two years. Two‐year PRS was 50% in patients without extraosseous dissemination, independent from localization. Conclusion: The BR rate was remarkable in asymptomatic EC survivors. A single bone was frequently involved. Little is known of the optimal treatment for metastatic bone disease in EC, thus, management should be individualized and patients should be encouraged to participate in clinical trials.